EDUCATING THE VERBAL SEMANTICS IN THE CONTEXT OF ACTANTIAL DISTRIBUTION - Sergey, Lazarev; Natalia, Semenova; Olga, Cherdyntseva (Gênero & Direito, 2020)
This study is based on the theory of methods of verbal action (MVA), presented in the works by O.M. Sokolov. Prefixed Russian verbs are considered as part of a functional approach to language analysis. The authors prove that the verb prefixes in the Russian language should be considered as separate linguistic elements, which provide the characteristics of the subject or object actant.